Concomitant heterochromatinisation and down-regulation of gene expression unveils epigenetic silencing of RELB in an aggressive subset of chronic lymphocytic leukemia in males - Marteau Jean-Brice; Rigaud Odile; Brugat Thibaut; Gault Nathalie; Vallat Laurent; Kruhoffer Mogens; Orntoft Torben F; Nguyen-Khac Florence; Chevillard Sylvie; Merle-Beral Hélène; Delic Jozo (BMC, 2010)
Abstract Background The sensitivity of chronic lymphocytic leukemia (CLL) cells to current treatments, both in vitro and in vivo, relies on their ability to activate apoptotic death. CLL cells resistant to DNA damage-induced apoptosis display deregulation of a specific set of genes. Methods Microarray hybridization (Human GeneChip, Affymetrix), immunofluorescent in situ labeling coupled with video-microscopy recording/analyses, chromatin-immunoprecipitation (ChIP), polymerase chain reactions (PCR), real-time quantitative PCR (RT-QPCR) and bisulfite genome sequencing were the main methods applied. Statistical analyses were performed by applying GCRMA and SAM analysis (microarray data) and Student's t-test or Mann & Whitney's U-test. Results Herein we show that, remarkably, in a resistant male CLL cells the vast majority of genes were down-regulated compared with sensitive cells, whereas this was not the case in cells derived from females. This gene down-regulation was found to be associated with an overall gain of heterochromatin as evidenced by immunofluorescent labeling of heterochromatin protein 1α (HP-1), trimethylated histone 3 lysine 9 (3metH3K9), and 5-methylcytidine (5metC). Notably, 17 genes were found to be commonly deregulated in resistant male and female cell samples. Among these, RELB was identified as a discriminatory candidate gene repressed in the male and upregulated in the female resistant cells. Conclusion The molecular defects in the silencing of RELB involve an increase in H3K9- but not CpG-island methylation in the promoter regions. Increase in acetyl-H3 in resistant female but not male CLL samples as well as a decrease of total cellular level of RelB after an inhibition of histone deacetylase (HDAC) by trichostatin A (TSA), further emphasize the role of epigenetic modifications which could discriminate two CLL subsets. Together, these results highlighted the epigenetic RELB silencing as a new marker of the progressive disease in males.